New genera of stiletto flies endemic to Madagascar (Therevidae: Therevinae) - Irwin, Michael E.; Winterton, Shaun L. (European Journal of Taxonomy, 2024)
Two new endemic genera of Therevinae are described from Madagascar. Rinhatiana gen. nov. contains three new species (R. arctifestuca gen. et sp. nov., R. cracentis gen. et sp. nov. and R. latifestuca gen. et sp. nov.) as well as R. distincta (Lyneborg, 1976) comb. nov., which is transferred from Stenopomyia Lyneborg, 1976. Tianarinha gen. nov. is described containing two new species, T. goodmani gen. et sp. nov. and T. micet gen. et sp. nov. All species are diagnosed and figured along with distribution data.